ACCELERATED OR SUPERFICIAL: A THEMATIC AND RHETORICAL ANALYSIS OF SPEED-READING PEDAGOGY ON INSTAGRAM AND FACEBOOK - Harahap, Rosni (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study employs a qualitative descriptive design to investigate the pedagogical approaches and persuasive strategies used in speed-reading instruction on Instagram and Facebook. In the digital age, where information overload is common, speed-reading has been repackaged as a marketable skill on social media platforms. This research analyzes content from selected influencers, utilizing a hybrid approach of thematic and rhetorical analysis. The findings reveal a distinct tension between the promises of accelerated learning and the potential for superficial understanding. Thematically, the content emphasizes techniques like skimming and chunking, while rhetorically, it heavily relies on emotional appeals (pathos) and credibility-building (ethos), often at the expense of logical evidence (logos). The study concludes that while social media provides accessible avenues for learning, the pedagogy of speed-reading on these platforms is frequently shaped by commercial incentives and the need for viral engagement, which can oversimplify complex cognitive processes. This research offers critical insights for educators and learners in navigating digital literacy instruction.